Evaluation of Nanomodified Asphalt with CaCO3: Rheological and Mixture Performance - Ahmed Mahir Mohammed; Alaa H. Abed (Communications, 2025)
The impact of using three contents of 1, 3 and 5 % of nano CaCO3 on the composition of asphalt binder and the mechanical properties of Hot Mix Asphalt (HMA) wearing course was studied. Laboratory tests were performed to examine the physical and rheological characteristics of nanomodified asphalt binder. In addition, Superpave Indirect Tensile Test (IDT) was conducted to evaluate the mechanistic characteristics and moisture susceptibility of the HMA. The test findings pointed that the nano modified asphalt with 5% nano CaCO3, decreased the temperature sensitivity due to asphalt stiffening and improved resistance to permanent deformation. Additionally, HMA mixture performance exhibits a substantial increase in moduli value at temperatures varying from 5 to 40 oC and increased flexibility at lower testing temperatures as compared to the neat HMA mixture.